Screening of exotic and indigenous apple rootstocks for different horticultural traits - Srivastava, KK; Singh, DB; Kumar, Dinesh; Mir, JI (SAARC Journal of Agriculture, 2017)
An experiment was carried out to find the suitable exotic as well as indigenous apple rootstocks for temperate zone of India. The rootstocks were screened on the basis of 11 important pomological traits. The data revealed that maximum numbers of primary and secondary roots were noted of 93.40, 92.76 in MM.106 and USA 106 and 92.0 noted in CITHrootstock- 01, respectively. Maximum length of primary roots (19.83cm) was recorded of EMLA 106 whereas shortest primary roots (6.47 cm) were recorded of ALNARP. The longest secondary roots (11.83cm) were found in M.27 and shortest secondary roots (2.10 cm) in ALNARP rootstock. Most of the indigenous apple rootstocks were having short to medium length of secondary roots. Leaf area was recorded highest (3.80cm2) in CITH-Apple rootstock-04 and smallest (1.96 cm2) of USA- 106. All the evaluated rootstocks have pink colored petiole except B-9, which has dark red color. Highest collar rot incidence was observed in M- 27 and M-26 and least in indigenous root stocks (CITH-Apple rootstocks). Highest wooly aphid infection was found in M-9, B-9, M-27, EMLA-106 and ALNARP whereas least infestation noted in M-26 and indigenous apple rootstock (CITH-ARS-01, CITH-ARS-02, CITH-ARS-03, CITH-ARS-04, CITH-ARS-, CITH-ARS-09 and CITH-ARS-10). Primary root length has positive correlation with secondary root numbers, secondary root length and leaf petiole length but negative correlation with leaf area. SAARC J. Agri., 14(2): 117-125 (2016)